CLT Classrooms: Teachers' Role & A Bangladesh Perspective - Tarannum, Sawsan (IIUC Studies, 2012)
This paper is designed to look at the role of teacher talk and teacher-student interaction in the management of communicative English learning. In particular, the focus is given on the activities of the teachers in a communicative English language classroom. For the organization of the classroom, teacher talk is of crucial importance. The language which teachers use is important for the organization and management of a communicative English language classroom, because it is the medium through which teachers either succeed or fail to implement their teaching plans. In this paper I have tried to discuss the role of a teacher in a communicative way. Teachers have to play different roles in CLT classrooms; therefore I will focus on their functions in general and their problems in the context of Bangladesh in particular. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12265 IIUC Studies Vol.7 2011: 131-146